Estimation of the discord time for a process of the Ornstein-Uhlenbeck type - Vovk, L. B.; Maiboroda, R. E. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A consistent estimate is constructed for the discord time of a process of the Ornstein-Uhlenbeck type. The rate of the almost sure convergence of this estimate is investigated and the confidence interval is determined.